Mechanisms of anaphylaxis in human low-affinity IgG receptor locus knock-in mice - Gillis, Caitlin M.; Jönsson, Friederike; Mancardi, David A.; Tu, Naxin; Beutier, Héloïse; Van Rooijen, Nico; Macdonald, Lynn E.; Murphy, Andrew J.; Bruhns, Pierre (Journal of allergy and clinical immunology, 2017)
Anaphylaxis can proceed through distinct IgE- or IgG-dependent pathways, which have been investigated in various mouse models. We developed a novel mouse strain in which the human low-affinity IgG receptor locus, comprising both activating (hFcγRIIA, hFcγRIIIA, and hFcγRIIIB) and inhibitory (hFcγRIIB) hFcγR genes, has been inserted into the equivalent murine locus, corresponding to a locus swap. We sought to determine the capabilities of hFcγRs to induce systemic anaphylaxis and identify the cell types and mediators involved. hFcγR expression on mouse and human cells was compared to validate the model. Passive systemic anaphylaxis was induced by injection of heat-aggregated human intravenous immunoglobulin and active systemic anaphylaxis after immunization and challenge. Anaphylaxis severity was evaluated based on hypothermia and mortality. The contribution of receptors, mediators, or cell types was assessed based on receptor blockade or depletion. The human-to-mouse low-affinity FcγR locus swap engendered hFcγRIIA/IIB/IIIA/IIIB expression in mice comparable with that seen in human subjects. Knock-in mice were susceptible to passive and active anaphylaxis, accompanied by downregulation of both activating and inhibitory hFcγR expression on specific myeloid cells. The contribution of hFcγRIIA was predominant. Depletion of neutrophils protected against hypothermia and mortality. Basophils contributed to a lesser extent. Anaphylaxis was inhibited by platelet-activating factor receptor or histamine receptor 1 blockade. Low-affinity FcγR locus-switched mice represent an unprecedented model of cognate hFcγR expression. Importantly, IgG-related anaphylaxis proceeds within a native context of activating and inhibitory hFcγRs, indicating that, despite robust hFcγRIIB expression, activating signals can dominate to initiate a severe anaphylactic reaction.